SURVIVAL AT PLAY: HOW VIDEOGAMES IMAGINE ENVIRONMENT (DECOLONIZATION NOT INCLUDED) - (:unkn) unknown (My University, 2024)
Videogame environments can range from familiar natural worlds rendered in two dimensions to fantastical 3D reimaginations, to the literary natural environments of text-based games. How videogames ask players to engage with their environments is often rooted in colonial frameworks of environmental domination and cultural erasure. My dissertation examines the intersections of Indigenous critical theory and representations of environment in how games interrogate survival—how do we survive, what does it mean to survive, and what are the conditions and implications of survival? My project centers Indigenous epistemologies of kinship, gratitude, and reciprocity to craft a framework for reading ecocolonial in/justice in videogame environmental design and narrative. The first chapter outlines an ontology of play rooted in the Anishinaabeg, Haudenosaunee, Ho-Chunk, Menominee, and Wabenaki traditional practice of weaving black ash baskets. Traditionally trained weavers explain that the first few rows of a basket’s base are critical to its ability to hold weight, and each row relies on the sturdiness of the others. In Braiding Sweetgrass, Citizen Potawatomi Nation botanist Robin Wall Kimmerer likens the three rows to Indigenous epistemologies of environment: a recognition of kinship with the natural world (the first row) facilitates deep gratitude for its power to sustain us (the second row) and cultivates responsibility to participate reciprocally among all our relations (the third row). I use this metaphor of weaving a basket of well-being as the roots of an ontological approach to game environments that emphasizes the implications of how games ask us to play at survival while eliding the colonial sources of environmental dangers exacerbated by the global climate crisis. I argue that these games’ environmental contingencies equip players to challenge or conform to colonial ideologies that privilege violence, oppression, and displacement by affording opportunities for players to practice land-based learning. Each subsequent chapter of my dissertation applies this ethic of the three rows to different game environments that center themes of survival through their narrative, mechanics, or reception. Taken holistically, my dissertation values the vitality of virtual environments, taking to task the way dangerous settler ideologies pervade the worlds we play in.
Keywords: Indigenous environmental justice; mino-bimaadiziwin; survival in video games; videogame environments